The Effectiveness of Play Therapy to Emotion, Behavior and Social on Adolescent Client in Mental Hospital - Heri Setiawan; Wahyu Tri Atmojo; Susi Rutmalem (Jurnal Ilmu Keperawatan Jiwa, 2020)
Mental health disorders in the first episode occur during adolescence. Data shows that 20-30% of adolescents experience depressive episodes before reaching adulthood. Between 50% and 75% of adolescents with anxiety, hyperactivity or ADHD disorders develop during adolescence. The suicide rate in adolescence ranks third in the cause of death in adolescents. To overcoming adolescent mental health problems in the Mental Hospital are through play therapy. The purpose of this study was to determine the effect of play therapy on emotions, behavior and social behavior in adolescent clients in psychiatric hospitals. The research method used is a quasi-experimental quantitative research with one intervention group, the sampling method with purposive sampling. Data collection tool using the SDQ questionnaire before and after given play therapy. Data were analyzed by statistical tests, the results of research conducted showed that play therapy has a positive effect on the emotional, behavioral and social status of adolescent clients in psychiatric hospitals with a p value <0.05. Play therapy can improve the signs of emotional, behavioral and social symptoms of adolescents in mental hospitals.